Evaluation De La Vulnérabilité Sismique Des Deux Casbahs De « Tigditt Et Derb-Tobbana » - MAARAF ZOUBIDA (My University, 2012)
The natural and anthropic disasters which have occurred in the last few years caused enormous losses for populations, buildinge and other infrastructures (communication and transport networks ), to human activities (economic , of leisures ,services …) and to the cultural and environmental heritage (monumemnts , landscapes , biodiversity… ) this latter represents in some how , the cultural essence of a country ; this is a legacy which helps the humanity to be a sounce of the seismic risk always constitutes a threat for this kind of infrastructures ,it is not only limited at the understanding of the geophysical risk that restults from this data « earthquake » but also from the understanding of its effect on the historical works which remains quite dimantary . Art and the way of making profitable knowledge to improve seismic safty of these existing works are surrounded by some uncertainties . The suggested approach in this fame work is based on some funamental points which vauatein , general , the various componets of the seismic risk , that is to say the presence of the risk in area of Mostaganem and the vulnerability of the builts composed mainly in buildings ,thus characterizing the architecture and the constructive mode taking place in the two ancient centres . Indeed ,the goal of the study is to disamount how the analysis of the vulnerability can provide answers to questionings to generate characters in terms of structural vulnerability . This analysis means the estimate of damage degree carried via a method of classification of the buildings known as « method of index of vulnerability » based on the development (benedetti on 1988) . This step is proceded systematically by an invertory established in-situby collection of parameters of structural and nonstructural of the samples. The findings and analysis that are made willing to build knowledge about vulnerability of buildings that constitute a fundamontal information and that can not make sense unless they are refrence to an objective which is natutance the preservation and protection of the heritage of future earthquakes and hence the enphasis in this work to defind when possible , interventions in the shorte medium and long term and proveding a nessecery improvements as well the heritage ,in its waintessing capacity of our history , and which can be transmitted to the future generations ,is based on an effective prevention judicious to the intervention means in a lower cost which can be , then managements tools of the heritage in the terms of the seismic risks decrease and long – stunding development
Keywords: Mostaganem, Derb-Tobbana andTijditt, seismic risk, vulnerability, heritage estate